Environmental Pollutants and Oxidative Stress in Terrestrial and Aquatic Organisms: Examination of the Total Picture and Implications for Human Health - Anetor, Gloria Oiyahumen; Nwobi, Nnenna Linda; Igharo, Godwin Osaretin; Sonuga, Oyebola Oluwagbemiga; Anetor, John Ibhagbemien (Frontiers in Physiology, 2022)
There is current great international concern about the contribution of environmental pollution to the global burden of disease particularly in the developing, low- and medium-income countries. Industrial activities, urbanization, developmental projects as well as various increased anthropogenic activities involving the improper generation, management and disposal of pollutants have rendered today’s environment highly polluted with various pollutants. These pollutants include toxic metals (lead, cadmium, mercury, arsenic), polycyclic aromatic hydrocarbons, polychlorinated biphenyls, pesticides and diesel exhaust particles most of which appear to be ubiquitous as well as have long-term environmental persistence with a wide range of toxicities such as oxidative stress among others. Oxidative stress, which may arise from increased production of damaging free radicals emanating from increased pollutant burden and depressed bioavailability of antioxidant defenses cause altered biochemical and physiological mechanisms and has been implicated in all known human pathologies most of which are chronic. Oxidative stress also affects both flora and fauna and plants are very important components of the terrestrial environment and significant contributors of nutrients for both man and animals. It is also remarkable that the aquatic environment in which sea animals and creatures are resident is also highly polluted, leading to aquatic stress that may affect the survival of the aquatic animals, sharing in the oxidative stress. These altered terrestrial and aquatic environments have an overarching effect on human health. Antioxidants neutralize the damaging free radicals thus, they play important protective roles in the onset, progression and severity of the unmitigated generation of pollutants that ultimately manifest as oxidative stress. Consequently, human health as well as that of aquatic and terrestrial organisms may be protected from environmental pollution by mitigating oxidative stress and employing the principles of nutritional medicine, essentially based on antioxidants derived mainly from plants, which serve as the panacea of the vicious state of environmental pollutants consequently, the health of the population. Understanding the total picture of oxidative stress and integrating the terrestrial and aquatic effects of environmental pollutants are central to sustainable health of the population and appear to require multi-sectoral collaborations from diverse disciplinary perspectives; basically the environmental, agricultural and health sectors.